2020
DOI: 10.1016/j.asmr.2020.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Costs, Complications, and Reoperations Associated With Primary Arthroscopic Rotator Cuff Repair With or Without Acromioplasty and/or Biceps Tenodesis

Abstract: To evaluate the reoperations, complications, and costs up to 5 years following arthroscopic rotator cuff repair (RCR) alone, with acromioplasty (acro), with biceps tenodesis (BT), or with both acro and BT. Methods: We queried the MarketScan database to identify patients who underwent RCR from 2007 to 2016. Patients were stratified into groups based on concomitant procedures (acro and/or BT) performed on the same day as index RCR. Reoperations, complications, and costs were followed for 5 years post-index proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 59 publications
0
7
1
Order By: Relevance
“…Compared to average complication rates from national registry data, we observed an increased rate of postoperative complications in our XRT-specific cohort (RCR 10.3%-17.2% 28,30 vs. 40%, arthroplasty 4%-14.2% 3,12 vs. 28.6%). Available data on the effects of XRT on shoulder surgical outcomes are overall lacking.…”
Section: Discussioncontrasting
confidence: 65%
“…Compared to average complication rates from national registry data, we observed an increased rate of postoperative complications in our XRT-specific cohort (RCR 10.3%-17.2% 28,30 vs. 40%, arthroplasty 4%-14.2% 3,12 vs. 28.6%). Available data on the effects of XRT on shoulder surgical outcomes are overall lacking.…”
Section: Discussioncontrasting
confidence: 65%
“…Flatow et al suggested that the normal AHI should be greater than 1 cm. [ 21 ] If it was less than 1 cm, it was considered a stenosis and the greater tubercles of the humerus would hit the acromion. [ 22 ] Some scholars believed that when AHI > 10.6 mm, the use of clavicular hook plate fixation generally did not cause SIS.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement and evaluation of the subacromial space of the patient was commonly referred to as acromion humeral interval (AHI). Flatow et al suggested that the normal AHI should be greater than 1 cm [21] . If it was less than 1 cm, it was considered a stenosis and the greater tubercles of the humerus would hit the acromion [22] .…”
Section: Discussionmentioning
confidence: 99%
“…9 Reported disadvantages of tenodesis include higher healthcare costs and a lack of consensus on the ideal surgical technique. [10][11][12][13] In addition, although rare (,1%), complications specific to tenodesis have been reported including loss of fixation, infection, hematoma, and complex regional pain syndrome. 13 The incidence of subsequent procedures after isolated rotator cuff repair (RCR) remains high.…”
mentioning
confidence: 99%